Optimal active control for fast response of temperature oscillation suppression in cryostats. (September 2022) - Chen, Hui; Wei, Chenxi; Hu, LuLu; Liu, Yingwen
Highlights: The PID temperature control method is applied in the cryostat with consideration of heat capacity hysteresis. The response of temperature oscillation under different PID modes is analyzed. The proper PID coefficients are given to satisfy the temperature stability of the cryostats. The temperature time series are unfolded in phase portraits and Poincaré maps to analyze the temperature fluctuation characteristics. Abstract: A fast response active temperature control method and ultra-high temperature stability in a cryostat are essential for the low-temperature primary gas thermometry. In this paper, numerical analysis models of the Proportional-Integral-Derivative (PID) active temperature control method on a cryocooler-based cryostat's performance with different coefficients are constructed. Furthermore, the heat capacity hysteresis is also considered to reduce temperature fluctuation further. The response of temperature oscillations under different PID modes is analyzed and compared to address the difficulty in accurately regulating the temperature oscillations. The system can quickly respond to the required temperature by predicting and optimizing the control coefficients. The flange temperature fluctuations are reduced by magnitude. We unfolded the temperature time series in phase portraits and Poincaré maps to identify the temperature fluctuation characteristics with different regulation coefficients. Numerical research in this paper realizes a faster response to disturbances with better temperature stability according to the dynamic characteristics of temperature fluctuation in the sample chamber. The pre-calculation of the control coefficient makes the heating power fluctuate in a small range, preventing overshoot and effectively reducing the percussion to the experimental equipment.